Correlates of burnout symptoms among child care teachers. A multilevel modeling approach. Issue 1 (2nd January 2018) - Blöchliger, Olivia R.; Bauer, Georg F.
ABSTRACT: Burnout is a widespread occupational stress outcome among child care teachers, jeopardizing the quality of care and children's development. This study aimed at exploring the relationships between individual and organizational level characteristics (representing the six work-life areas control, reward, workload, community, fairness, and values) and burnout levels because these nested associations are an overlooked area. We applied a mixed-effects model with data at the individual level (level 1) and child care center level (level 2) using assessments of 220 child care teachers and their 59 directors of 59 child care centers in a Swiss community. We found that the child care center mattered for the experienced burnout levels and that lower control and reward on level 1 and higher workload on level 2 were associated with higher burnout levels among child care teachers. These results suggest the need to target the individual and the organizational levels to tackle burnout symptoms.